Effectiveness of Hot Herbal Compress and the Waistband to Reduce Height the Fundus of Uterus - Widiyanti, Desi; Destariyani, Elvi; Yuniarti, Yuniarti; Yulyana, Nispi (Sarana Ilmu Indonesia (salnesia), 2024)
The disrupted recovery process of postpartum mothers can lead to subinvolution which is one of the causes of postpartum hemorrhage, with the current incidence rate in Indonesia 5% - 20% of deliveries. Treatment in the postpartum period is influenced by cultural factors in the community such as the use of waistband and hot herbal compresses. The purpose of this study was to determine the effectiveness of hot herbal compresses and the use of waistband to reduce the height of the uterine fundus. This research method is quantitative with a Quasi-experimental approach with two group pre-posttest design with a total sample of 60 postpartum mothers and taken by using purposive sampling technique. The results showed that the average decrease in uterine fundal height in the hot herbal compress group and the waistband group had a significant difference with p value <0,05. In conclusion, there was a more significant decrease in the height of the fundus of uterus by giving hot herbal compresses. It is hoped that the use of hot herbal compresses by postpartum mothers as an alternative non-pharmacological therapy.